2015
DOI: 10.1377/hlthaff.2014.0528
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Beneficiaries In California Reported Less Positive Experiences When Assigned To A Managed Care Plan

Abstract: In 2011 California began transitioning approximately 340,000 seniors and people with disabilities from Medicaid fee-for-service (FFS) to Medicaid managed care plans. When beneficiaries did not actively choose a managed care plan, the state assigned them to one using an algorithm based on their previous FFS primary and specialty care use. When no clear link could be established, beneficiaries were assigned by default to a managed care plan based on weighted randomization. In this article we report the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…8,23 Challenges with a burdensome enrollment process may be compounded by low Medi-Cal acceptance rates among providers and limited in-network providers within managed care plans. 24 Patients with Medi-Cal also reported a preference for receiving care in the ED or UC. Factors such as social instability and distrust of the health care system may contribute substantially to this theme, though systemic problems may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…8,23 Challenges with a burdensome enrollment process may be compounded by low Medi-Cal acceptance rates among providers and limited in-network providers within managed care plans. 24 Patients with Medi-Cal also reported a preference for receiving care in the ED or UC. Factors such as social instability and distrust of the health care system may contribute substantially to this theme, though systemic problems may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…New trends in the literature also considered quality variation within HMO managed-care programs. Researchers have shown that algorithms used to auto-assign Medicaid recipients to plans do not produce optimal matches (32,35). Evidence also indicated that high-risk recipients were more likely to switch to higher-quality plans than were low-risk recipients.…”
Section: Qualitymentioning
confidence: 99%
“…We could not determine from the data available whether an enrollee chose an MCO or was auto-enrolled. Research has shown that this affects enrollee experiences (McDonnell & Graham, 2015), and future research should include that variable in analysis of claims to determine whether choosing an MCO affects PCP and specialist utilization.…”
Section: Limitationsmentioning
confidence: 99%